A Novel Inflammatory Dendritic Cell That Is Abundant and Contiguous to T Cells in the Kidneys of Patients With Lupus Nephritis - Parikh, Samir V.; Malvar, Ana; Shapiro, John; Turman, James M.; Song, Huijuan; Alberton, Valeria; Lococo, Bruno; Mejia-Vilet, Juan M.; Madhavan, Sethu; Zhang, Jianying; Yu, Lianbo; Satoskar, Anjali A.; et al. (Frontiers in Immunology, 2021)
The mechanisms that promote local inflammatory injury during lupus nephritis (LN) flare are largely unknown. Understanding the key immune cells that drive intrarenal inflammation will advance our knowledge of disease pathogenesis and inform the development of new therapeutics for LN management. In this study, we analyzed kidney biopsies from patients with proliferative LN and identified a novel inflammatory dendritic cell (infDC) population that is highly expressed in the LN kidney, but minimally present in healthy human kidneys. During an agnostic evaluation of immune transcript expression in the kidneys of patients with proliferative LN, the most abundantly overexpressed transcript from isolated glomeruli was FCER1G, which encodes the Fc receptor gamma chain (FcRγ). To identify the cell types expressing FcRγ that infiltrate the kidney in LN, studies were done on kidney biopsies from patients with active LN using confocal immunofluorescence (IF) microscopy. This showed that FcRγ is abundantly present in the periglomerular (PG) region of the kidney and to a lesser extent in the tubulointerstitium (TI). Further investigation of the surface markers of these cells showed that they were FcRγ+, MHC II+, CD11c+, CD163+, CD5−, DC-SIGN+, CD64+, CD14+, CD16+, SIRPα+, CD206−, CD68−, CD123−, CD3−, and CD11b−, suggesting the cells were infDCs. Quantification of the infDCs showed an average 10-fold higher level of infDCs in the LN kidney compared to the healthy kidneys. Importantly, IF identified CD3+ T cells to be adjacent to these infDCs in the PG space of the LN kidney, whereas both cell types are minimally present in the healthy kidney. Thus, we have identified a previously undescribed DC in lupus kidneys that may interact with intrarenal T cells and play a role in the pathogenesis of kidney injury during LN flare.